An Overview of the Legal framework of Advanced Fee Fraud and Cybercrime in Nigeria - Mu’azu Abdullahi Saulawa (Faculty of Law, Hasanuddin University, 2016)
The paper seeks to discuss an overview on the advanced fee fraud offences as well as cybercrime in Nigerian. The aims of the paper focus on discussing the advanced fee fraud under the related provisions of Advanced Fee Fraud Act 2006 on the success of the law in addressing the practices of crimes in relation to information technology. The paper also discusses the cybercrimes in Nigeria with a brief look out on the Cybercrime (Prohibition and Prevention) Act 2015. Further, it also aims at examining the application of the law in the fraud offences which raises an issue of the regulatory framework of the cybercrime. The methodology adopted by the paper is doctrinal approach method wherein both primary and secondary sources of data were analysed, particularly the local laws and other relevant documents. The finding of the paper reveals that the relevant section of the in the Advanced Fee Fraud Act that deals with electronic communication has not been invoked. This is because the discussed relevant law under the advanced fee fraud did not in any away deal with cases concerning electronic communication under section 13. The paper recommends that there is a need to strengthen the adequacy of the legal framework on the Cybercrimes so as to checkmate such practices in Nigeria.